Pengaruh Penambahan Tepung Daun Kelor (Moringa Oleifera L.) pada Cokelat Putih sebagai Snack Alternatif Pencegahan Anemia pada Remaja Putri - Susan Paramita, Irma; Rahayu, Dewi; Erowati, Dewi; Atasasih, Hesti (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Moringa leaves contain many nutrients, one of which is iron. Insufficient iron intake can cause anemia in adolescents, because iron is an important element for the formation of hemoglobin. Moringa leaf flour can be used as a substitute ingredient for making food dishes. One of the foods that teenagers like to consume is chocolate. This research aims to determine the hedonic test of white chocolate with the addition of moringa leaf flour (Moringa oleifera L.). The type of research was experimental with a Completely Randomized Design (CRD) consisting of 4 treatments, namely 0%, 0.01%, 0.02%, and 0.03%. The research panelists were 25 panelists who were somewhat interested. Statistical analysis of differences in the hedonic test used was the Kruskal Wallis test (a≤0.05). The hedonic test results showed that the most preferred treatment was K2 treatment (0.02%). The results of statistical analysis showed that there were differences in hedonic tests in taste characteristics (p=0.018) and color (p=0.006), as well as no differences in aroma characteristics (p=0.872) and texture (p=0.163). The highest levels of iron and vitamin C in Moringa chocolate were obtained from treatment with the addition of 7.5 grams of Moringa leaf flour (K3). Based on the research results, it is recommended for further research to carry out new innovations, such as making snack bars with the addition of moringa leaf flour (Moringa oleifera L.) and continuing with antioxidant tests.